2016
DOI: 10.5370/jeet.2016.11.3.690
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the Dielectric, Physical and Chemical Properties of Palm Oil and Coconut Oil under Open Thermal Ageing Condition

Abstract: -In this paper, a study is carried out to investigate the dielectric, physical and chemical properties of Palm Oil (PO) and Coconut Oil (CO) under open thermal ageing condition. The type of PO used in this study is Refined Bleached and Deodorized Palm Oil (RBDPO) Olein. The ageing experiment was carried out at 85 °C and 115 °C for 1, 3, 5, 7 and 14 days. Several parameters were measured such as AC breakdown voltage, dielectric dissipation factor, relative permittivity, resistivity, viscosity, moisture and acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…A previous study [8] revealed that there is no apparent effect of the ageing on the physiochemical and electrical properties RBDPO at 115 °C under open conditions. However, the current study shows that several physicochemical and electrical properties of both RBDPO were affected by an ageing temperature of 170 °C under open conditions.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…A previous study [8] revealed that there is no apparent effect of the ageing on the physiochemical and electrical properties RBDPO at 115 °C under open conditions. However, the current study shows that several physicochemical and electrical properties of both RBDPO were affected by an ageing temperature of 170 °C under open conditions.…”
Section: Discussionmentioning
confidence: 90%
“…A previous study [8] revealed that there is no apparent effect of the ageing on the physiochemical and electrical properties RBDPO at 115…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…A study has been carried out to explore the performance of coconut oil as an insulator [11]. Investigation of different properties of Palm Oil (PO) and Coconut Oil (CO) has been carried out under open thermal ageing condition [12]. The analysis of breakdown strength and ASTESJ ISSN: 2415-6698 physical characteristics of extra virgin olive oil and castor oil under unaged and thermally aged conditions is performed and compared the results with mineral oil with respect to same aging process [13].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies also examine the partial discharge characteristics of RBDPO, as well as the effect of moisture and fat content on the breakdown voltage, dielectric dissipation factor, viscosity, and flash point of RBDPO [ 44 , 45 , 46 , 47 ]. A previous ageing study on RBDPO was carried out under open conditions and without the presence of insulation paper [ 48 ]. On the other hand, a few thermal ageing studies have been carried out on CO that focussed on the oil properties such as interfacial tension, acidity, AC breakdown voltage and dielectric properties [ 49 , 50 ].…”
Section: Introductionmentioning
confidence: 99%